Boosting Self-Powered Ultraviolet Photoresponse of TiO2-Based Heterostructure by Flexo-Phototronic Effects - Kumar, Mohit; Park, Ji Yong; Seo, Hyungtak (Advanced Optical Materials, 2022)
Ultraviolet photodetectors have long been used as key elements for various applications, including optical sensing and communication. However, accurate sensing of weak UV intensities under self-powered conditions with stable photocurrent and rapid temporal response remains critical because of challenges related to having suitable band alignment and strong junction quality. Here, an enhancement in the self-power ultraviolet (UV, λ = 365 nm) photoresponse of the silver nanowires/TiO2 Schottky photodetector is demonstrated by taking advantage of the flexoelectric phenomenon. The device does not show measurable photocurrent under self-biased conditions with low-intensity (200 µW cm–2) UV illumination, whereas a significant photocurrent of about 0.48 µA is measured by integrating the photovoltaic and flexo-phototronic effects. Additionally, rise/fall times improved from 300/1068 to 43/165 µs by utilizing the flexo-phototronic effects, depicting an enhancement of 597%. Further, remarkable responsivity of 124 mA W–1 and high detectivity of 6.5 × 1011 Jones under self-biased conditions are recorded. Moreover, microscopic evidence of flexoelectric effect modulated photoresponse is provided by photoconductive atomic force microscopy measurements. High efficiency and self-powered capability demonstrated in this study are likely to inspire the development of next-generation ultrafast, energy-efficient, and sophisticated photodetectors for communication, imaging, and sensing networks.
Keywords: Atomic-force-microscopy; Flexo-phototronic effect; High performance; Performance; Photoconductive atomic force microscopy; Photoresponses; Self-biased; Self-biased device; Self-powered; UV photoresponse; flexo-phototronic effect; high performance; photoconductive atomic force microscopy; photodetectors; self-biased devices; UV photoresponse